Love A - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
It appears that in our modern world with advanced and ubiquitous technology available to us, ironically, our ability to connect and to love one another and find love seems to be more illusive than ever. Are we born with an innate ability to give and receive love? Are we experiencing a crisis with regard to love at this time in history? And if so, how do we address this crisis? And is true altruism and unconditional love possible for human beings? This program explores love through the lens of science, medicine, religion and philosophy.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format.
Keywords: Love; Psychology, Religious